Efficacy of Levothyroxine (LT4) and Liothyronine (T3) Combination Therapy vs. LT4 Monotherapy for Hypothyroidism: A Meta-Analysis - Gede Made Cahya Trisna Pratama; Dewi Catur Wulandari (Bali Medical and Wellness Journal, 2026)
Background: Levothyroxine (LT4) monotherapy is the standard treatment for hypothyroidism, using serum thyroid-stimulating hormone (TSH) as the primary indicator of therapeutic adequacy. However, many patients remain symptomatic despite achieving normal TSH levels. Objectives: This meta-analysis evaluates the biochemical and metabolic efficacy of adding liothyronine (T3) to LT4 compared to standard monotherapy. Method: A systematic search was conducted to identify randomized controlled trials (RCTs) comparing LT4+T3 combination therapy with LT4 monotherapy in adults. TSH was the primary outcome, while secondary outcomes included free T4 (fT4), total T3, lipid profiles, and body weight. Results: Seven RCTs involving 355 participants were analyzed. Biochemical outcomes showed no significant difference in TSH suppression (P=0.40) or total T3 levels (P=0.38) between groups. Notably, LT4 monotherapy resulted in significantly higher fT4 levels (MD=0.27; 95%CI: 0.13, 0.40; P=0.0001). Regarding metabolic outcomes, combination therapy significantly improved LDL cholesterol (MD=4.79; 95%CI: 1.63, 7.96; P=0.003) with zero heterogeneity (I2=0%). A borderline significant trend toward weight reduction was also observed in the combination group (MD=-2.26; 95%CI: -4.52, 0.01; P=0.05). Conclusion: Compared to monotherapy, LT4+T3 combination therapy provides significant metabolic advantages, particularly in LDL reduction, while maintaining biochemical euthyroidism.